Learning human anatomy amid COVID-19 pandemic: A students' perspective - Halima Albalushi; Mohamed Al Mushaiqri; Ruqaiya Al Jabri (Wolters Kluwer Medknow Publications, 2021)
Introduction: Many countries adopted remote teaching upon the declaration of COVID-19 pandemic. Like many universities around the world, Sultan Qaboos University in the Sultanate of Oman shifted to emergency remote teaching (ERT) to contain the spread of the virus. In addition, anatomy classes were shifted to be taught online completely. This study aimed to explore students' perspective about the impact of COVID-19 pandemic on anatomy learning. Methodology: Students enrolled in anatomy courses during spring 2020 semester were asked to fill a questionnaire within 4 weeks of the end of online classes. The questionnaire included questions about students' perceptions and preferences about learning anatomy during ERT. Results: Findings indicated that coronavirus pandemic was disruptive to students' anatomy learning. Fulfilling courses requirements, home environment, internet connection, the anatomy knowledge without exposure to cadavers, and other resources in the lab were their main concerns. The reliability of internet connection was a major factor affecting their way of studying anatomy and selecting learning resources. Social media platforms were helpful in assisting students in their study and communication between themselves and their instructors. However, assessment and practical part teaching were not satisfactory to the students and they urge improvement. Conclusion: COVID-19 pandemic was disruptive to anatomy education. Internet connection was the major obstacles for the students, while the social media platforms were helpful tools in study and communication. Students urged improvement in the practical part teaching and assessment of the anatomy courses.